2020
DOI: 10.2174/1874350102013010181
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mathematical Anxiety Instruments with a Rasch Model Analysis

Abstract: Background: This study was motivated by a large number of students who feel anxious when dealing with mathematics, which is an unpleasant feeling characterized by the presence of worry, anxiety, confusion, and stress. Objective: This study aims to test the instruments of mathematical anxiety using Rasch Model analysis. Materials and Methods: The study used descriptive analysis with a cross-sectional design. Subjects of the study were elementary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Rasch modeling in the process of disclosing students' abilities has been widely used by previous researchers, among others, to measure students' critical thinking skills in STEM learning in elementary schools (Hamdu et al, 2020). In addition, it is used to develop mathematical anxiety instruments, character, and student confidence in elementary school students (Karlimah et al, 2020;Nur et al, 2020;Rusmana et al, 2020). Analysis of students' abilities in working on HOTS-based test questions can identify students' ability levels in working on these questions.…”
Section: Resultsmentioning
confidence: 99%
“…Rasch modeling in the process of disclosing students' abilities has been widely used by previous researchers, among others, to measure students' critical thinking skills in STEM learning in elementary schools (Hamdu et al, 2020). In addition, it is used to develop mathematical anxiety instruments, character, and student confidence in elementary school students (Karlimah et al, 2020;Nur et al, 2020;Rusmana et al, 2020). Analysis of students' abilities in working on HOTS-based test questions can identify students' ability levels in working on these questions.…”
Section: Resultsmentioning
confidence: 99%
“…Biased items could discriminate against individuals in other categories, leading to different results [33]. Therefore, the CSAI instrument could be used for all types of gender in victims of sexual violence.…”
Section: Validity Testmentioning
confidence: 99%
“…Some of these studies have shown that using the Rasch model can help teachers, instructors, and researchers in the educational assessment eld improve the analysis quality. Karlimah, Andriani, and Suryana stated that classical measurement theory, which uses raw data based on rating responses, cannot represent the original characteristics of quantitative data, which are a continuum [33]. The Rasch model could transform the ordinal response into a higher accuracy ratio on the probability principle [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis process through Rasch modeling in previous research was carried out in the development of character and anxiety instruments in elementary schools, so in this study it becomes a reference in the technical process of data processing (Nur et al, 2020;Karlimah et al, 2020) as well as in measuring thinking skills. critical students in elementary schools (Hamdu, et al, 2020).…”
mentioning
confidence: 99%